The effectiveness of using songs in teaching english langauge as a didactic method to help children from kindergarten to learn vocabulary at Antonio Jose de Sucre elementary school, in David City 2009 - Lezcano Samudio, Ingrid Magalys; Palma Candanedo, Evelyn Linette; Juarez, Elizabeth (David, Panamá : UDELAS, 2010)
The importance of this studyl begins by stablishing whether a study guide, a practical approach of learning the english language, and the use of songs in the target language are effective didactic resources that provides a better acquisicition of a second language in children of this age.
TABLE OF CONTENT DEDICATION ACKNOWLEDGEMENT TABLE OF CONTENT TABLES INDEX GRAPHICS INDEX ANNEX INDEX CHAPTER I CHAPTER II THEORETICAL FRAMEWORK 2.1. Organizational review of the institution observed 2.1.1. Historical background 2.1.2. Mission 2.1.3. Objective 2.1.4. Organization chart of the elementary school 2.2. Importance of music 2.2.1. In memory 2.2.2. In teaching and learning 2.3. Music as strategy tool 2.3.1. Reasons for using songs in ESL classroom 2.3.2. Importance of song selection 2.3.3. Rhynthm of the songs 2.3.3.1. Types of vocabulary learning 2.3.3.2. Selection of vocabulary 2.3.3.3. Vocabulary needs tobe linked to music 2.3.3.4. Promote of motivation 2.4. Strategies to use in teaching english to ESL students 2.4.1. Total physical response 2.4.2. Community language learning 2.4.3. Audiovisual method 2.4.4. Suggestopedia 2.4.5. Warm up 2.4.6. Memory game CHAPTER III METHODOLOGICAL FRAMEWORK CHAPTER IV FINDINGS AND INTERPRETATION OF RESULTS CHAPTER V CONCLUSION AND ANNEX Bibliography Annex
Incluye Table of content
Documento presentado para optar por el título de Licenciatura en Docencia en Inglés
Incluye Bibliografía
No se presta a domicilio
No se saca fotocopia
Keywords: ENGLISH -- TESIS DE LICENCIATURA -- DIDACTIC; SONGS -- TESIS DE LICENCIATURA -- DIDACTIC METHOD; FACULTAD DE EDUCACIÓN SOCIAL; DEPARTAMENTO DE INGLÉS; ANTONIO JOSÉ DE SUCRE - ELEMENTARY SCHOOL - DAVID